Making research skill development explicit in coursework : final report. - Willison, John; Le Lievre, Kerrie; Lee, Irene (Australian Learning and Teaching Council, 2010)
Undergraduate and Masters by Coursework courses can explicitly and effectively develop student research skills, with both immediate and long-term advantages for both students and academics. This project was designed to trial and evaluate the effectiveness of coherent, explicit and incremental development of discipline-specific student research skills in content-rich courses, as informed by the Research Skill Development Framework (RSD). The project aimed to build a large research team across all faculties in five Australian universities in order to trial the RSD in as many disciplines and types of courses as possible. Two specific research questions were asked: What are the advantages and disadvantages of explicitly developing students' research skills? What factors support student research skill development, and what factors hinder its development? [Executive summary, ed]